Impasse and interpretation : therapeutic and anti-therapeutic factors in the psycho-analytic treatment of psychotic, borderline, and neurotic patients - Rosenfeld, Herbert A. (New library of psychoanalysis, 1987)
Herbert Rosenfeld makes a powerful case both for the intelligibility of psychotic symptoms and the potential benefits of their treatment by psychoanalytic means.